Supply Chain Risk Mapping at ABC Cement Plant in Aceh, Indonesia - Raihan Dara Lufika; Hasan Yudie Sastra; Prima Denny Sentia; Ilyas Ilyas; Iskandar Hasanuddin (Graduate Program of Syiah Kuala University, 2022)
Supply Chain Risk Management is an industry collaboration work with partners in the supply chain system to implement a risk management process in dealing with the emergence of risks and uncertainties caused by logistics activities or other resources in the supply chain. Every industry deals with risk. This study aims to identify, classify, and mapping supply chain activities and their risks. At the initial stage, the identification of supply chain events is done by doing interviews and brainstorming. Then, these events are portrayed in the supply chain map. Then, the risk identification stage used a rating scale to determine the level of likelihood and consequence based on three SCOR elements. There are 40 risk events in this study which are 13 risk events in the source section, 19 risk events in the make section, and eight risk events in the delivery section. Finally, it is necessary to calculate the value of the Risk Priority Index (RPI). The RPI is the basis of the risk mapping stage. The risk map will show the urgency to treat each risk event.